Evidencing How Experience and Problem Format Affect Probabilistic Reasoning Through Interaction Analysis - Reani, Manuele; Davies, Alan; Peek, Niels; Jay, Caroline (Frontiers in Psychology, 2019)
This paper examines the role that lived experience plays in the human capacity to reason about uncertainty. Previous research shows that people are more likely to provide accurate responses in Bayesian tasks when the data are presented in natural frequencies, the problem in question describes a familiar event, and the values of the data are in line with beliefs. Precisely why these factors are important remains open to debate. We elucidate the issue in two ways. Firstly, we hypothesise that in a task that requires people to reason about conditional probabilities, they are more likely to respond accurately when the values of the problem reflect their own lived experience, than when they reflect the experience of the average participant. Secondly, to gain further understanding of the underlying reasoning process, we employ a novel interaction analysis method that tracks mouse movements in an interactive web application and applies transition analysis to model how the approach to reasoning differs depending on whether data are presented using percentages or natural frequencies. We find 1) that the closer the values of the data in the problem are to people's self-reported lived experience, the more likely they are to provide a correct answer, and 2) that the reasoning process employed when data are presented using natural frequencies is qualitatively different to that employed when data are presented using percentages. The results indicate that the benefits of natural frequency presentation are due to a clearer representation of the relationship between sets and that the 'prior' humans acquire through experience has an overwhelming influence on their ability to reason about uncertainty.